Collected Stories - Hanif Kureishi (London Faber and Faber, 2010)
"Over the course of the last decade, Hanif Kureishi has written short fiction. The stories are, by turns, provocative, erotic, tender, funny and charming as they deal with the complexities of relationships as well as the joys of children." "This collection contains his controversial story Weddings and Beheadings, a well as his prophetic My Son the Fanatic, which exposes the religious tensions within the Muslim family unit." "As with his novels and screenplays, Kureishi has his finger on the pulse of the political tensions in society and how they affect people's everyday lives. This collection contains eight new stories."--Jacket.
Keywords: Noveller